"VIRTUUM" AS AN INNOVATIVE SPHERE IN THE "DIGITAL CIVILISATION" (PHILOSOPHICALEPISTEMOLOGICAL AND ONTOLOGICAL ASPECTS) - Kharchenko, Julia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
It is confirmed that virtuum is entirely artificial and its space-time is an antinomy. This means that while virtuum is limited by current technological possibilities, it is not limited by imagination and fantasy. Virtual reality is just one of the multiple manifestations of virtuum, which is a special innovative environment reflecting the transformation of modern knowledge in the rapidly changing reality of the "technical body." This transformation occurs at the "collision" of a multitude of "logics," "rationalities," "simulacrums," and "phantasms," all of which are visualized in this reality. The phenomenon of virtuum as a special innovative environment, where the transformation of modern knowledge takes place, is conceptualized. By analyzing the mechanism of vergence, which is a factor that provides synchrony of processes and phenomena in imaginary and actual realities, as well as a point of intersection of divergent and convergent processes, it is possible to understand the "third," middle state of virtuum as a complex "digital" system.